Wrinkled nitrile rubber films for stretchable and ultra-sensitive respiration sensors. (February 2017) - Yu, Yan; Ye, Lei; Song, Yongming; Guan, Yaodong; Zang, Jianfeng
Abstract: Respiration pattern (including both breath rate and intensity) is critical vital symptoms of many disorders such as sleep apnea, asthma, chronic obstructive pulmonary disease, and anemia. Breath sensors that can distinguish abnormalities in breath patterns can ascertain the basic human body conditions during sleep, exercise, sports and surgery play a significant role in healthcare system and have attracted more and more attentions. However, the existing breath sensors are limited in the sensitivity and not compatible with the practical applications during movements. Here we present a simple approach employing the wrinkled nitrile rubber films to detect the human respiration, both breath rate and intensity The three-dimensional wrinkled structure of nitrile rubber films could significantly increase the capability to distinguish different intensities of respiration, with an average intensity ratio of 16 times for strong breath over weak breath signal These sensors also show fast response (up to 2 Hz) high sensitivity, and can be stretched by 100% with stable breath sensing property. Our respiration sensors are favorable to the urgent healthcare monitoring applications in the near future.